PHYTOREMEDIATION AND EXTRACTION OF COLLOIDAL CONTAMINANTS FROM MINE EFFLUENTS THROUGH LEGUME PLANTS - Velichka Arahangelova; Alexandre Loukanov (Sustainable Extraction and Processing of Raw Materials Journal, 2023)
The bioaccumulation and environmental toxicity of colloidal contaminants have always been the focus of extensive research. Here we report efficient extraction of iron oxide colloidal contaminants from mine drainage effluents by phytoremediation with legume plants. The smallest fine particles with size less than 10 nm exhibit two wide absorption peaks at 350 and 495 nm, respectively. They have good dispersibility in aqueous environment and are highly resistant to removing or purification by any gravitational settings. The ultra-small nanosized particles (with average diameter 2-3 nm) can be bioaccumulated into the roots of soybean sprouts and might cause physiological stress and inhibition of the germination process. All experimental data found delayed growth, as well as decreased biomass production, which was observed in both the stem and root system of treated sprouts. Nevertheless, the immersed in mine effluent plants showed some resistance to the colloid toxicity. The light microscopic analysis also revealed the occurrence of more intensive symbiosis between the root tubers and the rhizosphere microbial communities in the case of phytorenmediation. The absorbance spectroscopic measurement demonstrated about 90 % efficient colloidal removement from the suspension within 10 days treatment. The atomic absorption spectroscopy analysis of mineralised sprouts cultured in synthetic mine effluents found that the highest concentration of accumulated iron in the legume plants was 258,02 ± 23,48 mg/100 g, which was achieved in suspension of 25 mM FeSO4. The presented report enables potential practical application of legume plants in the circumneutral passive treatment systems for remediation of mine effluents.